A note on operations of intuitionistic fuzzy soft sets - Jayanta Ghosh; T. K. Samanta; Sankar Kumar Roy (Journal of Hyperstructures)
In this article, it an achievement for our part to be had of notions of a few operations on intuitionistic fuzzy soft sets and generalization of De Morgan's laws with respect to some operations in intuitionistic fuzzy soft set theory\,. It is being validated by suitable example. Thereafter properties like associative, distributive relative to different operations on intuitionistic fuzzy soft set are established and justified by suitable example\,. It is shown that restricted symmetric difference operation does not satisfy associative and restricted intersection does not distribute over restricted symmetric difference in intuitionistic fuzzy soft set theory.